Hepatic pathology of biliary atresia: A new comprehensive evaluation method using liver biopsy - Zhang, Shouhua; Wu, Yan; Liu, Zhiwen; Tao, Qiang; Huang, Jinshi; Yang, Wenping (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: Despite its unique pathological characteristics, biliary atresia (BA) has no consensus pathological grading system. Therefore, the purpose of this study was to propose a new pathological grading system and to compare the diagnostic value of intraoperative frozen and postoperative paraffin-embedded liver sections. Materials and Methods: A total of 81 BA patients were analyzed for clinical and biochemical data, immunohistochemistry, and routine postoperative histology and intraoperative frozen pathology sections. Bile duct hyperplasia was classified into three grades (B1–B3), and fibrosis was classified into four classical grades (F1–F4). Results: The patients included 41 males and 40 females, aged 35–150 days. The repartition, in terms of severity, of small bile duct hyperplasia and fibrosis was as follows: B1, 21 cases; B2, 41 cases; B3, 19 cases; F1, 1 case; F2, 11 cases; F3, 51 cases; and F4, 18 cases. Both grades were statistically correlated. When comparing intraoperative frozen and postoperative paraffin-embedded sections, the overall diagnostic concordance rate was 97.5%. Conclusion: The new proposed pathological grading system may be useful for the diagnostic and prognostic assessment of BA. In addition, intraoperative frozen liver tissue biopsy samples represent a valuable and promising adjunct to the conventional postoperative paraffin-embedded sections.